Mesenchymal Stem Cells: Characteristics, Function, and Application - Li, Zhongjun; Hu, Xingbin; Zhong, Jiang F. (Stem cells international, 2019)
[...]novel strategies for maintaining, and even promoting, the biological activities and therapeutic capabilities of MSCs are really needed. J. Zhan et al. reported that fasudil, a potent rho kinase inhibitor, significantly enhanced the migration ability of bone marrow MSCs via activation of the MAPK signaling pathway, promoting MSC homing to the spinal cord injury site. [...]we would like to express our deep gratitude to the reviewers for their valuable contributions to this special issue.